Genetic variants within the serotonin transporter associated with familial risk for major depression. Issue 1 (30th July 2015) - Talati, Ardesheer; Guffanti, Guia; Odgerel, Zagaa; Ionita-Laza, Iuliana; Malm, Heli; Sourander, Andre; Brown, Alan S.; Wickramaratne, Priya J.; Gingrich, Jay A.; Weissman, Myrna M.
Abstract: The role of the serotonin transporter promoter linked polymorphism (5HTTLPR) in depression, despite much research, remains unclear. Most studies compare persons with and without depression to each other. We show offspring at high ( N =192) as compared to low ( N =101) familial risk for major depressive disorder were almost four times as likely to have two copies of the short allele at 5HTTLPR, suggesting that incorporation of family history could be helpful in identifying genetic differences. Highlights: Genetic studies of depression typically compare persons with the disorder to those without. We show that serotonin transporter genotypes vary by familial risk for depression. Incorporating family history may help identify genetic variants for depressive disorders.